Life-threatening Q fever infection following exposure to kangaroos and wallabies. (17th September 2015) - Stevenson, Sarah; Gowardman, John; Tozer, Sarah; Woods, Marion
Abstract : A 28-year-old woman, a park ranger, developed acute Q fever with associated sepsis, profound jaundice, disseminated intravascular coagulation and multiorgan failure necessitating prolonged admission to the intensive care unit for ventilatory support. She recovered fully and remains well 4 years later.